An Investigation Comparing the Efficacy of Topical Ocular Application of Tacrolimus and Cyclosporine in Dogs. (23rd May 2011) - Hendrix, Diane V .H.; Adkins, Elizabeth A.; Ward, Daniel A.; Stuffle, Jamie; Skorobohach, Brian
Abstract : The purpose of this paper was to determine the efficacy and safety of topical tacrolimus, compared to cyclosporine, for treating keratoconjunctivitis sicca (KCS) in dogs. This study was a two-phase, randomized, controlled, masked clinical trial. Phase 1 evaluated ophthalmic 0.03% tacrolimus in normal dogs. Ocular examinations were performed daily. Phase 2 evaluated the efficacy of tacrolimus in treating KCS. Half the dogs received 2% cyclosporine A; the others received 0.03% tacrolimus, both diluted in olive oil. Four ophthalmic examinations were done over 12 weeks. There was no significant difference between groups in phase I. In phase 2, there was no significant difference in Schirmer tear test I (STT) results between the two groups, and both groups had a significant increase in STT over time. Both drugs were effective in increasing the STT in dogs naïve to lacrimostimulants. Tacrolimus was effective in increasing the STT in 4 dogs currently nonresponsive to cyclosporine.